The training methods and leg muscle strength on students' upper pass volleyball learning outcomes - Muhammad Zeki; Nurul Ihsan; Alnedral Alnedral; Nuridin Widya Pranoto (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
This study examined the effects of paired and independent overhead passing training methods in relation to leg muscle strength on the overhead passing ability of school-level volleyball athletes. A quantitative experimental design with a 2×2 factorial pretest–posttest approach was employed. Twenty-four students participating in a volleyball extracurricular program were classified into high and low leg muscle strength groups and assigned to paired or independent training. Overhead passing ability was measured before and after the intervention using a standardized skill test. Data were analyzed using paired samples t-tests to identify within-group changes. The results showed a significant improvement only in athletes with high leg muscle strength who received paired training (p < 0.05), while other groups showed no significant changes. These findings suggest that overhead passing improvement depends on the interaction between training method and physical readiness. Further studies with larger samples and factorial analyses are recommended.